Geomechanical Characterization of a Host Rock for Enhanced Geothermal System in the North-German Basin. (2017) - Alber, M.; Solibida, C.
Abstract: The North-German Basin offer at depth of approximately 5000 m sufficiently high temperatures for efficient and economic heat extraction by geothermal wells. The permeability of the carboniferous strata at that depth is very low so that conductive pathways have to be created by hydraulic fracturing. For some planned projects we conduct the characterization of the carboniferous strata as exposed in "analogous outcrops". The geological setting for fracking is demanding, as the strata comprise strong sandstone, shale and weak coal seams. All necessary petrophysical properties will be collected by extended testing. The regional horst-and-graben system allows for mapping in outcrops and extrapolate the structural content towards the rock mass at depth.